2011
DOI: 10.1177/0149206311425612
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Entrepreneurial Orientation in the Task Environment–Performance Relationship

Abstract: Despite the importance of the external task environment for firm performance, little is known about the mechanisms that enable firms to benefit from a specific environmental setting. The authors argue that firms adjust their entrepreneurial orientation (EO) to the external environment and use it as a mechanism to transform the advantages provided by the environment into above-average performance levels. Specifically, the authors use meta-analysis supplemented by structural equation modeling to explore the link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
390
2
22

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(438 citation statements)
references
References 95 publications
24
390
2
22
Order By: Relevance
“…However, as in most research on EO (Rosenbusch et al 2013), we do not demonstrate causal links because only qualitative methods allow for the establishment of causality. SMEs with better financial performance can thus be better positioned to develop SD practices (Dixon-Fowler et al 2013;Orlitzky 2008).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 88%
“…However, as in most research on EO (Rosenbusch et al 2013), we do not demonstrate causal links because only qualitative methods allow for the establishment of causality. SMEs with better financial performance can thus be better positioned to develop SD practices (Dixon-Fowler et al 2013;Orlitzky 2008).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 88%
“…It has been argued that EO can be regarded as a multi-dimensional construct (Lumpkin and Dess, 1996); however, it has been equally suggested that EO is a unidimensional construct, and it should be analysed as such (Covin and Slevin, 1991). Meta-analyses of the entrepreneurship literature reveals that most studies have summed across innovativeness, proactiveness and risk taking to create an individual dimension of EO (Rauch et al, 2009;Rosenbusch et al, 2013). Further, it was found that these three dimensions are of equal importance explaining organizational performance across most studies, and thus it is reasonable to support the use of a summed index in future research (Covin et al, 2006;Rauch et al, 2009;Tang et al, 2009).…”
Section: Manufacturing Capabilities Organizational Performance and Ementioning
confidence: 99%
“…Organizations respond to external environments (e.g., environmental munificence, hostility, complexity and dynamism) by entrepreneurial behaviour, which helps to exploit opportunities provided by the environment (Khandwalla, 1987;Rosenbusch et al, 2013). Specifically, entrepreneurial behaviour influences strategic decisions and actions that enable firms to successfully translate resources into capabilities to suit the environment (Rosenbusch et al, 2013).…”
Section: Manufacturing Capabilities Organizational Performance and Ementioning
confidence: 99%
See 2 more Smart Citations